College EFL teachers’ demotivation to conduct research: A dynamic and ecological view - Ren, Xiaobin; Zhou, Fen (Frontiers in Psychology, 2023)
Competences for conducting research is vitally important for college EFL teachers’ career development, but many college English teachers are demotivated in academic research. To investigate those teachers’ motivation on academic activities, this study firstly explored their motivational levels for conducting research in their teaching career, and then delved into the factors underlying their demotivation by sending questionnaires. In the end, several English teachers and officers managing research projects were interviewed to elicit solutions to overcome EFL teachers’ demotivation to conduct research. This study found that college EFL teachers had large possibilities to suffer from demotivation to conduct research. Exploratory factor analysis indicated five factors causing their demotivation, including weak research ability, negative emotions and attitudes, poor research surroundings, research management problems and insufficient resources. Thematic analysis demonstrated that ecological solutions should be taken by different stakeholders in EFL teachers’ working ecology, including universities, research communities, government, and publishers. This study problematized the static view on teachers’ demotivation to conduct research and provided some insights and implications for reasons and solutions for demotivation.